Usefulness of a long sheath in ureteral catheterization after failure of antegrade ureteral stent placement using a short sheath. (December 2021) - Chen, Cheng Shi; Kim, Jong Woo; Shin, Ji Hoon; Li, Hai-Liang; Lee, Hyung Jin; Ibrahim, Alrashidi; Jang, Eun Bee
Background: When antegrade ureteral intervention fails due to severe ureteral stricture or tortuosity, a longer sheath can be used to facilitate ureteral catheterization. Purpose: To evaluate the feasibility and effectiveness of the use of a long sheath in antegrade ureteral stent placement after failure of antegrade ureteral stent placement using a short sheath. Material and Methods: Among 1284 procedures in 934 patients who received ureteral stent placement, a long sheath was used after stricture negotiation failure using a short sheath in 57 (4.4%) procedures in 53 patients. The data of these 53 patients were retrospectively reviewed. Results: The most common reasons for long sheath use were failure of balloon catheter (59.6%) or guidewire (29.8%) advancement across the stricture. Technical success, successful stricture negotiation after using a long sheath, was achieved in 50/57 (87.7%) procedures. In two of seven failed procedures, an additional TIPS sheath was used and the technical success rate improved to 91.2% (52/57). The technical success rate was significantly higher in the patients who have failed balloon catheter advancement (97.1%, 33/34) than the patients who have failed guidewire advancement (64.7%, 11/17) (Fisher's exact test, P  = 0.004). Self-limiting hematoma occurred in one patient after use of the long sheath and was considered a minor complication. Conclusion: Ureteral catheterization using a long sheath is feasible and effective when antegrade ureteral intervention using a short sheath fails. When using a long sheath, the technical success rate was higher when advancing the balloon catheter over the guidewire than when advancing the guidewire through tight stricture.